Mitul jertfei creatoare din balada Mănăstirea Argeșului reinterpretat în opera rock-simfonică Meșterul Manole (2013) – o analiză din perspectivă socio-istorică și intermedială - Bartosiewicz-Nikolaev, Olga (Studia Romanica Posnaniensia, 2023)
The main objective of my paper is to present the sociopolitical circumstances of the creation of the rock-symphonic opera Meșterul Manole (2013), based on a libretto by Victor Cârcu and composed by Joseph Kappl (former member of the rock band Phoenix), its reception by contemporary society and its character as an intermedial work. In my study, I will use the tools of the intermedial approach, which will help me to describe and grasp the relations of transposition of the myth between different media that interact and influence each other in the opera under analysis.